Continuity and Change – One Hundred Years of Polish Countryside. : Interdisciplinary Cooperation of Humanities and Social Sciences For Academic Dialogue - Stanny, Monika (Eastern European Countryside, 2024)
Continuity and Change – One Hundred Years of Polish Countryside. Interdisciplinary Cooperation of Humanities and Social Sciences For Academic Dialogue